2016
DOI: 10.3390/s16101702
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Energy Efficient Topology Control Scheme Based on a Coverage-Preserving and Sleep Scheduling Model for Sensor Networks

Abstract: In high-density sensor networks, scheduling some sensor nodes to be in the sleep mode while other sensor nodes remain active for monitoring or forwarding packets is an effective control scheme to conserve energy. In this paper, a Coverage-Preserving Control Scheduling Scheme (CPCSS) based on a cloud model and redundancy degree in sensor networks is proposed. Firstly, the normal cloud model is adopted for calculating the similarity degree between the sensor nodes in terms of their historical data, and then all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…To show the efficiency of the SAS protocol and validate its powerful in energy saving and extending the network lifetime, this section explains several experiments based on a data set conducted from Intel Berkeley Research Lab [11] and by using OMNeT++ network simulator [12]. Figure 3 shows a Sensor deployment in the Intel Berkeley Research Lab, as shown in this Figure, there is one sink node at the center of the Lab.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To show the efficiency of the SAS protocol and validate its powerful in energy saving and extending the network lifetime, this section explains several experiments based on a data set conducted from Intel Berkeley Research Lab [11] and by using OMNeT++ network simulator [12]. Figure 3 shows a Sensor deployment in the Intel Berkeley Research Lab, as shown in this Figure, there is one sink node at the center of the Lab.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In [10], the authors propose an iterative heuristic method called (IAND) to find the correlationdominating set for WSNs and greedy method to obtain the best nodes. In [11] the authors propose a Scheduling method called (CPCSS) that depends on the similarity model for calculating the correlation degree between the data of sensor nodes and partition the nodes into different classes. The redundancy degree among the nodes is calculated according to their sensing area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two factors significantly affect the power consumption of battery-powered IoT devices and sensors: radio transmissions, and channel access. However, the amount of power consumed by the MAC layer can be reduced, e.g., by reducing the amount of idle listening, duty cycling [ 52 ], implementing sleep scheduling [ 53 ]; and assigning priority slots for low-power devices [ 54 ].…”
Section: Design Considerations For Mac Protocols Of Uiotmentioning
confidence: 99%
“…Currently, mobile Ad hoc sensor network is widely utilized and obtains extensive applications for its rapid development, which results in the large quantities of problems emerged for the bad working condition [35][36][37]. For example, nodes in the network are likely to suffer from battery out of charge for the increasing power consuming rate and the link failure in the network.…”
Section: Fault Detection Algorithmmentioning
confidence: 99%